Life Cycle Analysis of Operational Energy in Office Projects Toward Sustainability Practices in the Malaysian Construction Industry - Moayedi, Farzaneh; Amila Wan Abdullah Zawawi, Noor; Shahir Liew, Mohd (International Journal of Engineering and Technology, 2018)
Global warming mitigation is used as a requisite key to promote approaches and sustainable policies in developing countries that aim to minimize the level of carbon emission in built environment. In the past few years, energy demand has grown enormously in Malaysia. CO2 emission from energy consumption, mainly from electricity is a stark condemnation of commercial sector. Building operational energy particularly the thermal aspect, is the dominant factor that used to be highlighted and investigated due to the fact that it is the main proportion of operational energy consumption in buildings. The rate of energy dissipation in building components depends on design and environmental conditions. Accordingly, actions need to be taken in order to promote the quality of buildings in terms of heat exchanges, which can lead to a signiï¬cant energy saving. Using of appropriate thermal insulation is effective way to diminish greenhouse gas emissions by reducing energy consumption. Therefore, the aim of the study is to investigate and determine the total amount of energy consumption from an office building. For reliability purposes, energy consumption from operation of baseline building was compared with the eco-friendly existing office building. Results show that, after implementation of sustainable solutions in the case study, operational energy consumption was successfully reduced to a grate extend.Â